Portuguese Heart Failure Prevalence Observational Study (PORTHOS) rationale and design – A population-based study - Baptista, Rui (2023)
Introduction and objectives: Current epidemiological data on heart failure (HF) in Portugal derives from studies conducted two decades ago. The main aim of this study is to determine HF prevalence in the Portuguese population. Using current standards, this manuscript aims to describe the methodology and research protocol applied. Methods: The Portuguese Heart Failure Prevalence Observational Study (PORTHOS) is a large, three-stage, population-based, nationwide, cross-sectional study. Community-dwelling citizens aged 50 years and older will be randomly selected via stratified multistage sampling. Eligible participants will be invited to attend a screening visit at a mobile clinic for HF symptom assessment, anthropomorphic assessment, N-terminal pro-B-type natriuretic peptide (NT-proBNP) testing, one-lead electrocardiogram (ECG) and a sociodemographic and health-related quality of life questionnaire (EQ-5D). All subjects with NT-proBNP ≥125 pg/mL or with a prior history of HF will undergo a diagnostic confirmatory assessment at the mobile clinic composed of a 12-lead ECG, comprehensive echocardiography, HF questionnaire (KCCQ) and blood sampling. To validate the screening procedure, a control group will undergo the same diagnostic assessment. Echocardiography results will be centrally validated, and HF diagnosis will be established according to the European Society of Cardiology HF guidelines. A random subsample of patients with an equivocal HF with preserved ejection fraction diagnosis based on the application of the Heart Failure Association preserved ejection fraction diagnostic algorithm will be invited to undergo an exercise echocardiography. Conclusions: Through the application of current standards, appropriate methodologies, and a strong research protocol, the PORTHOS study will determine the prevalence of HF in mainland Portugal and enable a comprehensive characterization of HF patients, leading to a better understanding of their clinical profile and health-related quality of life.